Application Value of Combined Detection of NLR, PNI, D-Dimer, CD3+ T Lymphocytes, and CEA in Colorectal Cancer Screening. (20th March 2022) - Ding, Rui; Chen, Zheng; He, Ming; Cen, Hong; Liu, Zehui; Su, Yonghui
Abstract : Objective. To investigate the application value of combined detection of neutrophil-lymphocyte ratio (NLR), prognostic nutrition index (PNI), D-dimer (D-D), CD3 + T lymphocytes (CD3 + T), and carcinoembryonic antigen (CEA) in colorectal cancer screening. Methods . The study cohort comprised 187 colorectal cancer patients and 100 mixed hemorrhoids patients as controls from January 2019 to August 2021 at the Fifth Affiliated Hospital of Sun Yat-sen University. Comparing the levels of NLR, PNI, D-D, CD3 + T, and CEA between the two groups of subjects, drawing receiver operating characteristic (ROC) curve evaluates the efficacy of single and combined detection for colorectal cancer screening. Results . Compared with the control group, the levels of NLR, D-D, and CEA in the colorectal cancer group were significantly increased, while the levels of PNI and CD3 + T were significantly decreased (P < 0.05 ). ROC curve analysis showed that the combined detection of NLR, PNI, D-D, CD3 + T, and CEA for colorectal cancer screening had an AUC ROC of 0.943, a sensitivity of 84.49%, a specificity of 91.00%, and a Youden index of 0.75, and its screening efficacy was significantly superior to that of a single detection (P < 0.001 ). Conclusion . The combined detection of NLR, PNI, D-D, CD3 + T, and CEA has a high clinical application value for colorectal cancer and can provide a reference for early screening and auxiliary diagnosis of colorectal cancer.